Foot Length as a Predictor of Weight in Children up to Five Years (TAJ: Journal of Teachers Association, 2019)
Weight measurement is essential for the management of pediatric patients to calculate the dose of the drugs. But it is not possible to move the child to a weighing scale for determination of body weight when the child is in a critical condition. The purpose of this study was to check if foot length correlates with child’s body weight in our situation and to devise a formula for prediction of weight based on foot– length observed. This Cross-sectional study was carried out in the Department of Pediatrics, Sir Salimullah Medical College, Mitford hospital, Dhaka over a period of 12 months between January 2008 and December 2008. A total of 300 children, between 0 day to five years, meeting the predefined eligibility criteria were included in the study. Using the available data, simple linear regression analysis was performed between the dependent variable weight and independent variable foot length. The estimated linear regression line was: Predicted weight (kg) = a+ [b× foot length]. Data were analyzed using correlation coefficient (r) between foot length and children’s weight. In this study correlation between foot length and weight (r) was 0.92(P